A role of MR Elastography in Assessment of Liver Fibrosis in North in India in tertiary care centre - Dr Karan Singh, Dr Phool Singh Sagar, Dr Aneeta Agrahari (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Liver fibrosis is a common outcome of various chronic liver diseases,including viral hepatitis, alcohol-related liver disease, and non-alcoholic fatty liverdisease (NAFLD). If left untreated, progressive fibrosis can lead to cirrhosis